2015
DOI: 10.1016/j.pmn.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Primary Dysmenorrhea and Factors Associated with Its Intensity Among Undergraduate Students: A Cross-Sectional Study

Abstract: Primary dysmenorrhea is a womanhood problem around the world and negatively affects quality of life. This study was designed to investigate the prevalence of primary dysmenorrhea and to determine the factors associated with its intensity. A cross-sectional study was carried out among 311 undergraduate female students aged 18 to 27 years in Isfahan University of Medical Sciences, Iran. Socio-demographic characteristics and menstrual factors were obtained through interviews with the help of a pretested questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
70
3
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 17 publications
16
70
3
17
Order By: Relevance
“…Among the 269 women who submitted their responses to the questionnaire, a high prevalence (84.01%) of painful menstruation was found, in quantitative agreement with the report by Grandi et al22 and with observations from other previous studies 8,10,14,15. While other studies have reported a lower prevalence of PD,11,13,17 the findings of the present survey are within the range of 20%–90% reported worldwide 13.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among the 269 women who submitted their responses to the questionnaire, a high prevalence (84.01%) of painful menstruation was found, in quantitative agreement with the report by Grandi et al22 and with observations from other previous studies 8,10,14,15. While other studies have reported a lower prevalence of PD,11,13,17 the findings of the present survey are within the range of 20%–90% reported worldwide 13.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of PD was investigated in different parts of the world and was found to vary with the geographical location. Specifically, the prevalence of PD was reported at 87.8% and 72.7% among university students in Turkey,8,9 89.1% in Iran,10 65% in India,11 76% in Malaysia,12 and 60% in Canada 13. In Arab countries such as Oman, Iraq, Lebanon, and Saudi Arabia, the reported prevalence of PD was 94%,14 89.4%,15 74.3%,16 and 60.9%, respectively 17.…”
Section: Introductionmentioning
confidence: 98%
“…In some, the Andersch and Milsom scale has been used, which considers dysmenorrhea as a menstrual pain that needs analgesic drugs or causes poor functioning (8)(9)(10)(11)(12). Some have used pain rating scales such as the Numeric Pain Rating Scales (NPRS) and Visual Analog Scale (VAS), which define primary dysmenorrhea as pain scores more than zero (13)(14)(15). Others have used the researcher-made scales in which mild to moderate menstrual pain have been considered as dysmenorrhea (6,(16)(17)(18).…”
Section: Contextmentioning
confidence: 99%
“…This figure is relatively higher than prevalence reported by Shah et al [10], Yasir et al [18] and Pejcic et al [20]. In contrasts, the prevalence was relatively lower in studies conducted by Teshome et al [8], El-Hameed et al [11], Mohamed et al [13], Chia et al [14], Khodakarami et al [15], Habibi et al [16] and Sidi et al [17]. The possible reasons for the discrepancy among the estimates could be the difference in the life style of study subjects, the difference in use of selected age group, difference in perception of pain during menstruation, the absence of universally accepted technique of defining dysmenorrhea, a probable disparity in the methods of data collection, study definitions of dysmenorrhea and pain.…”
Section: Discussionmentioning
confidence: 64%
“…Study conducted in Iraq revealed that the frequency of dysmenorrhea was estimated to be 85.31% [15]; likewise, a cross-sectional study carried among female students aged 18 to 27 years in Isfahan University of Medical SciencesIran, the prevalence was 89.1% [16]. Study conducted in Parakou high school showed that the prevalence of primary dysmenorrhea was 78.35% with 95% CI [74.07-82.11%].…”
Section: Introductionmentioning
confidence: 99%